What Is Driving the Rise in Advanced Economy Bond Yields? - Goel, Rohit (International Monetary Fund, 2021)
The nominal bond yields for advanced economies rose sharply during the first quarter of the year. This note analyzes the drivers of this increase across the jurisdictions and tenors of the yield curve. A key investor focus, in particular, has been the rise in the nominal bond yields in the United States, which has had notable global financial stability spillovers. The analysis indicates that the rise in inflation expectations is the primary driver of the rise in US nominal bond yields over the near term, whereas, the rise in real yields has been the major contributor to the rise in longer-term yields. The change in term premiums has also played a key role in driving both the longer-term inflation breakeven and real yields. Considering other major advanced economies, while inflation expectations have risen across the board in the near term, change in real yields appear more pertinent a driver for shifts in longer-term yields.